Proyecto de factibilidad para la creación de una empresa de servicio de limpieza y aseo para la ciudad de Zamora, Provincia de Zamora Chinchipe. - Mejía Encalada, Neiroby Viviana (2012)
The city of Zamora in recent years has experienced considerable population growth, being the capital of the province of Zamora Chinchipe, needs to be addressed in all its services, which is why a company toiletries and household cleaning, is one of the business options through which to generate economic resources to the benefit of the members, and the human resources that depend directly and indirectly on the activities undertaken by this company. That is why the new generation of professionals we have to make efforts to create small innovative companies, occupying the local workforce, with resources in the area and with products that may hit the market in top condition, quality and price, competing with the like who come from other provinces or cities, causing even more unemployment and jobs. From here the real need to produce goods and services, being enterprising and facing the grave crisis facing our country, being convenient to carry out and execute our thesis project called "PROJECT FEASIBILITY FOR THE CREATION OF A COMPANY AND TOILET CLEANING SERVICE CITY OF ZAMORA province of Zamora Chinchipe ", it contributes to the development of the county and the province of Zamora Zamora Chinchipe. To determine the project's feasibility study addressed the market through field research, scientific research using techniques such as literature, observation, surveys and interviews, which allowed them to obtain reliable information related to demand and supply. Then in the Technical Study highlights the size and location of the company, the process for the implementation of the service description and distribution processes, identifying areas to occupy and where the company is located. We also carried out the coupling process engineering the following criteria: Local distribution, product features, marketing process flow chart of processes, materials and equipment for normal operation. The legal and administrative organization was performed by applying the legal principles of the Law, and determined the operating functions for each of the existing jobs in the company and it was the company name as a limited company "CLEAN MORE” Subsequently, the study establishes financial investments requiring project of $ 84,759.75 for initiation, then determined the cost structure, the study of income, yielding a net profit for the first year of $ 54,136.51 while cash flow is $ 66,893, also raises the financial evaluation in order to know how the project is feasible, which calculates the Net Present Value (NPV) amounting to $ 325,449.89, the Internal Rate of Return (IRR) 80.68% higher than the rate of opportunity, the cost-benefit ratio (RB / C) is $ 1.90, the period Capital Recovery (PR / C) is achieved in one year and three months and in the sensitivity analysis shows that the project will allow an increase of 53.70% in costs and a 28.30% decrease in revenue. Finally conclusions are drawn with respective recommendations obtained in developing the project.